Computational Study of Metal-Free Magnetism and Spin-Dependent Seebeck Effect in Silicene Nanoribbons with Zigzag and Klein Edges - Xingyi Tan; Gang Xu; Youchang Jiang; Dahua Ren (Advances in Condensed Matter Physics)
Nanoribbons based on low-dimensional materials are potential candidates for nanoscale spintronics devices. Here, some ferromagnetic silicene nanoribbons with zigzag and Klein edges (N-ZKSiNRs) are constructed. It is demonstrated that the N-ZKSiNRs with various widths (N) are placed in various spin-resolved electronic situations. With the increase of the width parameter N from 4 to 19, the N-ZKSiNRs pass from the indirect-gap bipolar magnetic semiconducting state (BMS) to the bipolar spin-gapless semiconductor (BSGS) and eventually to half-metallicity (HM). Moreover, applying a temperature gradient through the nanoribbons leads to spin-dependent current with the opposite flowing and spin orientations, demonstrating the spin-dependent Seebeck effect (SDSE). Besides, it was found that the BSGS phase is superior to the BMS and HM for generating SDSE. These findings confirm that the ZKSiNRs are promising choices for spin caloritronics devices.